Peranan Pendampingan UMKM Untuk Meningkatkan Usaha Dan Akses Pasar Pedagang SWK Urip Sumoharjo - Andramaya Kusuma Ningtyas; Yanda Bara Kusuma (Pusat Riset dan Inovasi Nasional, 2024)
Assistance for Micro, Small and Medium Enterprises (MSMEs) plays a crucial role in improving business and increasing market access for traders at the Urip Sumoharjo Culinary Tourism Center, Surabaya. This research aims to explore the impact of the MSME mentoring program carried out by students from the MSIB program of the Surabaya City Cooperatives, Small and Medium Enterprises and Trade Service in strengthening business capacity, expanding markets, and improving the economic welfare of traders at SWK Urip Sumoharjo. Data collection techniques in this research involve direct observation and interviews in the field to identify obstacles and business conditions of traders in SWK Urip Sumoharjo, as well as literature studies to support the data obtained. The objects of this research include 20 SWK Urip Sumoharjo traders. Research findings show that mentoring which includes product management, finance, HR and digital marketing training significantly increases traders' businesses. Apart from that, the mentoring program has also succeeded in opening wider market access through the use of social media as a means to market the products of SWK Urip Sumoharjo traders.